The balance of power between Russia and NATO in the Arctic and High North - Kaushal, Sidharth (Routledge Journals, 2022)
The resurgence of Russian power in the Arctic and High North will be a key consideration for NATO planners. The Alliance's northern flank represents both a potential vulnerability due to its relative isolation and an area in which NATO enjoys options for horizontal escalation in a conflict. Moreover, as the effects of climate change create opportunities for both navigation and resource extraction, peacetime control over the Northern Sea Route (NSR) and a contest to establish effective administrative control in this area are likely. Disagreements regarding the degree of Russia's jurisdiction over the NSR could, for example, simmer into a form of sub-threshold competition. The purpose of this Whitehall Paper will be to examine the balance of power between NATO and Russia in this critical region in order to establish the level of ambition that the capabilities being developed by Russia can support.